Endoscopic Resection Improved High-Intensity Focused Ultrasound Ablation Outcomes for Prostate Cancer: A Meta-Analysis of Comparative Studies - Pan, Yang; Wang, Shangren; Zhou, Hang; Niu, Shuai; Liu, Xiaoqiang (Urology Journal, 2023)
Purpose: High-intensity focused ultrasound ablation (HIFU) is emerging as more data on its efficacy arises for prostate cancer (PCa). However, it is indefinite whether to combine endoscopic resection and uncertain to say who the ideal candidates are for the combined treatment. Therefore, we aimed to conduct a meta-analysis to compare outcomes of sole HIFU therapy with that of HIFU in combination with endoscopic resection in patients with localized PCa. Materials and Methods: Electronic databases were searched following the PRISMA guidelines and PICOS formats. The inclusion criteria were as follows: 1) studies on HIFU for PCa patients; 2) comparative studies on HIFU in combination with endoscopic resection for localized PCa men. Exclusion criteria include non-comparative studies and salvage HIFU therapy. Meta-analysis results were mainly present using forest plots. Sensitivity analysis and Egger’s test were adopted to determine the stability and assess the publication bias. Results: Six comparative studies with 767 patients were eligible, including 487 cases in the combination therapy group and 280 cases in the monotherapy group. There was no statistical difference in age, preoperative PSA levels, and prostate volume between two groups. No statistical difference was found in postoperative PSA nadir (MD = -0.02, 95%CI: -0.35 to 0.31, P = 0.90), disease-free survival rate (RR = 0.95, 95%CI: 0.83 to 1.09, P = 0.47), and preoperative IPSS score (MD = -0.69, 95%CI: -1.63 to 0.26, P = 0.15; I2 = 8%) between two groups. The combination therapy group had significantly lower postoperative IPSS score (MD = -5.49, 95%CI: -6.47 to -4.51, P < 0.001) and shorter catheterization time (MD=-13.70, 95%CI: -19.24 to -8.16, P < 0.001) than the monotherapy group. The rates of urinary incontinence (7.4% vs. 13.9%, RR = 0.45, 95%CI: 0.29 to 0.70, P = 0.0004; I2=4%), acute urinary retention (6.8% vs. 10.5%, RR=0.36, 95%CI: 0.14 to 0.89, P = 0.03; I2 = 0%), urinary tract infection (10% vs. 33%, RR = 0.27, 95% CI: 0.18 to 0.4, P < 0.001; I2 = 0%), epididymitis (1.2% vs. 15.7%, RR=0.11, 95% CI: 0.02 to 0.59, P = 0.01; I2 = 0%), and urethral stricture (7.1% vs. 23.2%, RR = 0.3, 95%CI: 0.18 to 0.51, P < 0.001; I2 = 0%) in the combination therapy group were all significantly lower than that in the monotherapy group. Sensitivity analysis revealed findings were convincing and no publication bias (P = 0.62) was observed using Egger’s test. Conclusion: It appears that the addition of endoscopic resection to the HIFU operation might not impact oncologic outcomes and could show better functional outcomes compared to the HIFU monotherapy in localized PCa patients.